(untitled) (Homoeopathy for All, 2024)
Jaundice, derived from the French word "jaune," meaning yellow, is a common medical condition that can occur in individuals of all ages. It results from an imbalance in bilirubin metabolism due to various pathological processes affecting the liver, biliary tract, or red blood cells. Bilirubin, a yellow pigment derived from the breakdown of heme, accumulates in the blood and tissues when its production or clearance is disrupted, leading to Jaundice. While neonatal Jaundice is often benign, Jaundice in adults usually indicates a significant underlying condition. A systematic understanding of its pathophysiology and causes is crucial for appropriate diagnosis and treatment.